Collins COBUILD school of American English - 4 0 16; 5 (Boston, MA : Thomson Heinle, 2008)
This new dictionary is for students studying in English-speaking schools, who are also learners of English. It is particularly suitable for students learning American English. This edition includes a CD-Rom, with extra content and interactive activities.
Keywords: 2 -- 0; 6; Dictionaries.;Dictionaries, Juvenile. -- English language;English language; 20; 2